2004
DOI: 10.1007/s00415-004-0483-3
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric aspects of Parkinson?s disease

Abstract: In patients with Parkinson's disease (PD) disturbances of mental state constitute some of the most difficult treatment challenges of advanced disease, often limiting effective treatment of motor symptoms and leading to increased disability and poor quality of life. This article provides an update on the current knowledge of these complications and the use of old and new drugs in their management. Mental state alterations in PD include depression, anxiety, cognitive impairment, apathy, and treatment-related psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
1
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(105 citation statements)
references
References 92 publications
4
93
1
7
Order By: Relevance
“…The age-related and progressive signs of PD classically include resting tremor, muscular rigidity, abnormal gait, and slow movement; however, other signs and symptoms associated with parkinsonism can include somatosensory deficits, impaired cognitive function, and psychiatric disturbances (2)(3)(4). Many PD signs result from the degeneration of dopaminergic neurons in the substantia nigra pars compacta.…”
mentioning
confidence: 99%
“…The age-related and progressive signs of PD classically include resting tremor, muscular rigidity, abnormal gait, and slow movement; however, other signs and symptoms associated with parkinsonism can include somatosensory deficits, impaired cognitive function, and psychiatric disturbances (2)(3)(4). Many PD signs result from the degeneration of dopaminergic neurons in the substantia nigra pars compacta.…”
mentioning
confidence: 99%
“…The gradual process of increase in resistance to b-lactams is shown by MIC values. Since the 1990s, decreased susceptibility rates to penicillin have been described in many countries, with prevalence rates sometimes higher than 40 % and, occasionally, MICs higher than 8 mg ml 21 (Appelbaum, 2002;Klugman, 1990;Schrag et al, 2004). Nevertheless, in the past few years, some studies have detected a significant decrease in the rates of resistant pneumococci in Europe and the USA with the introduction of the 7-val conjugate vaccine together with a reduction in antibiotic consumption levels (Doern et al, 2005;Kaplan et al, 2004;Oteo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…According to several cross-sectional surveys, rates of depression range from 20-50 % in PD patients [60]. Some studies have shown that compared with AD patients PDD patients display higher rates of major depression [63] and depressive symptoms [30,45].…”
Section: Behavioral Changes Associated With Pddmentioning
confidence: 98%